A roadmap to develop dementia research capacity and capability in Pakistan: A model for low‐ and middle‐income countries - Iracema Leroi; Nasim Chaudhry; Anna Daniel; Ross Dunne; Saima Eman; Nicolas Farina; Sana‐e‐Zehra Haidry; Nusrat Husain; Hussain Jafri; Salman Karim; Tayyeba Kiran; Murad Khan; et al. (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Objective To produce a strategic roadmap for supporting the development of dementia research in Pakistan. Background While global research strategies for dementia research already exist, none is tailored to the specific needs and challenges of low‐ and middle‐income countries (LMIC) like Pakistan. Methods We undertook an iterative consensus process with lay and professional experts to develop a Theory of Change‐based strategy for dementia research in Pakistan. This included Expert Reference Groups (ERGs), strategic planning techniques, a “research question” priority survey, and consultations with Key Opinion Leaders. Results We agreed on ten principles to guide dementia research in Pakistan, emphasizing pragmatic, resource sparing, real‐world approaches to support people with dementia, both locally and internationally. Goals included capacity/capability building. Priority research topics included raising awareness and understanding of dementia, and improving quality of life. Conclusion This roadmap may be a model for other LMIC health ecosystems with emerging dementia research cultures.